Awards and public perception: exploring the relationship between the evolution of American military awards and the changing American public - Danielbrigg, Anthony (Kansas State University, 2024)
The use of awards by the United States military is a tradition dating back to the American Revolutionary War. Since their inception, awards have been either adapted or created to suit the needs of the military of the time. Common among these needs are attempts to influence the American people’s perception of the government and military. The American public’s support, or lack thereof, has consistently been a cause for concern for the military, as public support is wanted, if not needed, for successful military actions. Looking at the evolution of the military’s repertoire of awards alongside public perception allows for the analysis of how the two have related throughout the history of the United States. Tracing which awards are introduced or altered by era, alongside the public opinion of the era, shows how the military responded to the changing beliefs of the public. The Medal of Honor is prevalent among these awards, both as a well-studied subject and as an award with clear alterations over its existence, and as such, provides a focused case study furthering the argument of the thesis. Looking at the history of American military awards, and the Medal of Honor specifically, alongside the changes in American public opinion, highlights the interplay between the two as the military attempts to influence the public.
Keywords: American public opinion; Medal of honor; American military awards; American home front; United States armed forces